Assessment of Post-Operative Pseudophakic Glaucoma by Ultrasound Biomicroscopy - Ragab IT (Dove Medical Press, 2020)
Islam Taher Ragab, Amr Mohammed Elsayed Abdelkader, Hanem Mohammad Kishk, Abdelmohsen Abdelghany Elshal Ophthalmology Department, Faculty of Medicine, Mansoura University, Mansoura, EgyptCorrespondence: Amr Mohammed Elsayed AbdelkaderDepartment of Ophthalmology, Mansoura University Ophthalmic Center, Faculty of Medicine, Mansoura University, B.O:35516, Mansoura, EgyptTel +20 1004314242Fax +20 502256104Email dramrabdelkader@gmail.comPurpose: Pseudophakic glaucoma is a secondary glaucoma in which intra-ocular pressure is elevated following cataract removal. The current study aimed to evaluate the role of ultrasound biomicroscopy (UBM) in assessing post-operative pseudophakic glaucoma.Patients and Methods: This is a case series, prospective, observational and analytical study. It included 29 eyes of 29 patients with post-operative pseudophakic glaucoma. The patients were evaluated by medical history, detailed ophthalmologic examination and UBM.Results: UBM examination has unmasked different causes of pseudophakic glaucoma. The detected causes were classified into 3 main groups, including intraocular lens (IOL)-related causes, lens remnants and intra-ocular inflammation. Haptic-related causes were present in 9 eyes, while 6 eyes had decentered or tilted IOLs. Soemmering’s ring was the main cause in 3 eyes while in one eye the cause was lens particle in the anterior chamber (AC). Silicone oil in AC with seclusio pupillae was the main cause in one eye. Peripheral anterior synechiae were detected in 8 eyes while, posterior synechiae were evident in 7 eyes. Uveitis induced by anterior chamber IOL (ACIOL) was found in 3 eyes and one eye had peripheral anterior synechiae due to neovascular glaucoma.Conclusion: UBM is a helpful diagnostic tool to evaluate causes of pseudophakic glaucoma through adequate visualization of different angle structures.Keywords: ultrasound biomicroscopy, UBM, pseudophakic glaucoma, hyphaema, neovascularization